Improved performance in national-level runners with increased training load at 1600 and 1800 m - Sharma, A. P.; Saunders, P. U.; Garvican-Lewis, L. A.; Clark, B.; Welvaert, M.; Gore, C. J.; Thompson, K. G. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To determine the effect of altitude training at 1600 and 1800 m on sea-level (SL) performance in national-level runners. Methods: After 3 wk of SL training, 24 runners completed a 3-wk sojourn at 1600 m (ALT1600, n = 8), 1800 m (ALT1800, n = 9), or SL (CON, n = 7), followed by up to 11 wk of SL racing. Race performance was measured at SL during the lead-in period and repeatedly postintervention. Training volume (in kilometers) and load (session rating of perceived exertion) were calculated for all sessions. Hemoglobin mass was measured via CO rebreathing. Between-groups differences were evaluated using effect sizes (Hedges g). Results: Performance improved in both ALT1600 (mean [SD] 1.5% [0.9%]) and ALT1800 (1.6% [1.3%]) compared with CON (0.4% [1.7%]); g = 0.83 (90% confidence limits -0.10, 1.66) and 0.81 (-0.09, 1.62), respectively. Season-best performances occurred 5 to 71 d postaltitude in ALT1600/1800. There were large increases in training load from lead-in to intervention in ALT1600 (48% [32%]) and ALT1800 (60% [31%]) compared with CON (18% [20%]); g = 1.24 (0.24, 2.08) and 1.69 (0.65, 2.55), respectively. Hemoglobin mass increased in ALT1600 and ALT1800 (~4%) but not CON. Conclusions: Larger improvements in performance after altitude training may be due to the greater overall load of training in hypoxia compared with normoxia, combined with a hypoxia-mediated increase in hemoglobin mass. A wide time frame for peak performances suggests that the optimal window to race postaltitude is individual, and factors other than altitude exposure per se may be important.